Pengaruh Profitabilitas, Leverage, Kepemilikan Institusional Dan Kepemilikan Manajerial Terhadap Pengungkapan Islamic Social Reporting Dengan Ukuran Perusahaan Sebagai Varaibel Moderating Pada Bank Umum Syariah 2016-2020 - Ismi Nurjanah (Jurnal Akuntansi dan Keuangan Kontemporer (JAKK), 2021)
The purpose of this study was to determine the Effect of Profitability, Leverage, Institutional Ownership and Managerial Ownership on Islamic Social Reporting (ISR) with Company Size as Moderating Variable in Islamic Commercial Banks for the 2016-2020 Period. This type of research is quantitative with moderating regression analysis used in the data. The total population in this study were 14 Islamic Commercial Banks. Purposive sampling technique was used in sampling, the sample in this study amounted to 12 Islamic Commercial Banks with secondary data. The test of this research is statistical test through t test, f test, r2, regression test and MRA test. The t-statistic test of this study resulted in the Profitability variable having a significant positive effect on ISR Disclosure, the Leverage variable having an insignificant negative effect on the ISR disclosure, the Institutional Ownership variable having a significant positive effect on the ISR Disclosure, the Managerial Ownership variable having an insignificant negative effect on the ISR Disclosure, while the MRA results only shows that the Firm Size variable is only able to moderate the effect of Institutional Ownership on ISR Disclosures, the Company Size variable is not able to influence the Profitability, Leverage, and Managerial Ownership variables on ISR Disclosure.